KEPIMPINAN DAN PROSES KAWALAN TERHADAP PERUNTUKAN KEWANGAN SEKOLAH: PERSPEKTIF MALAYSIA - Muhammad Faizal A. Gani; Norfariza Mohd Radzi; Saedah Siraj; Faisol Elham (Prodi Manajemen Pendidikan Jurusan Administrasi Pendidikan Fakultas Ilmu Pendidikan UNY, 2010)
Managing school finance is a complex task, especially when the country experienced slight economic downturn. Thus, all stakeholders should involve in helping the government to control the available financial allocation. At school level, school leaders, particularly principals should play a key role in line with the environmental changes such as global economic influence. Among main role as being discussed in this paper is to regulate the school allocation in order for financial management to be implemented in a prudent, efficient and effective way. To achieve that, the principals themselves should have good personality for example in the accountability of school financial management. This good personality derives from the stabilization of divine knowledge and knowledge of financial management. Furthermore, principals should also establish the Internal Control System to ensure that financial flows are well controlled. This is due to the capability of action plan to become a tool in controlling the approved allocation. In the action plan, the school leaders will spend the allocation based on the established procedures. It starts from identifying the need to purchase the property and assets allocation until the assessment on achievement of objectives. If the allocation spent has met the initial goals, it is considered to be a prudent, efficient and effective financial management. On the contrary, if the allocation spent has strayed beyond the initial goal, then the school leaders need to improve the early stages of management. As an implication, the school activities are in accordance with the approved allocations. The role of Internal Audit Unit should also be actively carried out by the school leaders. They are individuals who have skills in finance and free from the influence of the school. As an implication of the role of principal, school leaders will be able to improve the school outcome and restore the system as a whole.